DNase SISPA-next generation sequencing confirms Schmallenberg virus in Belgian field samples and identifies genetic variation in Europe. - Rosseel, Toon; Scheuch, Matthias; Höper, Dirk; Nick De Regge; Frank Vandenbussche; Steven Van Borm (PLoS One, 2012)
In 2011, a novel Orthobunyavirus was identified in cattle and sheep in Germany and The Netherlands. This virus was named Schmallenberg virus (SBV). Later, presence of the virus was confirmed using real time RT-PCR in cases of congenital malformations of bovines and ovines in several European countries, including Belgium. In the absence of specific sequencing protocols for this novel virus we confirmed its presence in RT-qPCR positive field samples using DNase SISPA-next generation sequencing (NGS), a virus discovery method based on random amplification and next generation sequencing. An in vitro transcribed RNA was used to construct a standard curve allowing the quantification of viral RNA in the field samples. Two field samples of aborted lambs containing 7.66 and 7.64 log(10) RNA copies per µL total RNA allowed unambiguous identification of SBV. One sample yielded 192 SBV reads covering about 81% of the L segment, 56% of the M segment and 13% of the S segment. The other sample resulted in 8 reads distributed over the L and M segments. Three weak positive field samples (one from an aborted calf, two from aborted lambs) containing virus quantities equivalent to 4.27-4.89 log(10) RNA copies per µL did not allow identification using DNase SISPA-NGS. This partial sequence information was compared to the whole genome sequence of SBV isolated from bovines in Germany, identifying several sequence differences. The applied viral discovery method allowed the confirmation of SBV in RT-qPCR positive brain samples. However, the failure to confirm SBV in weak PCR-positive samples illustrates the importance of the selection of properly targeted and fresh field samples in any virus discovery method. The partial sequences derived from the field samples showed several differences compared to the sequences from bovines in Germany, indicating sequence divergence within the epidemic.
Keywords: Belgium; Deoxyribonucleases; DNA Primers; Genetic Variation; High-Throughput Nucleotide Sequencing; Molecular Sequence Data; Nucleic Acid Amplification Techniques; Orthobunyavirus; RNA, Viral; Sequence Analysis, RNA